PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI INDONESIA SEBELUM DAN SETELAH KRISIS - Ari Mulianta Ginting; Rasbin Rasbin (Jurnal Ekonomi & Kebijakan Publik, 2010)
In the period of 1970‐1996 the poor in Indonesia was reduced, but the monetary crisis in 1997 had increased due to the declining of economic growth. The purpose of this study is to analyze the economic growth that influence poverty in Indonesia. The time regression analysis showed the effect of economic growth to the unemployment and poverty in Indonesia. It is also shown that there was significant positive relations between GDP and poverty rate, but it was negative and significant relation between government expenditure (GE) and poverty. Therefore, government expenditure (GE) should be increased because of is associated with the reduction of poverty in Indonesia.